CHEMICALLY INDUCED EMULSION POLYMERIZATION OF METHACRYLIC ACID ESTER WITH DIETHYLETHYNYL CARBONATE IN THE PRESENCE OF NON-IONIC EMULSIFIERS OP-10 - Sharipov Sh.R.; Ruziev I.Kh.; Salimova G.B.; Ergashev E. (Journal Park Publishing, 2023)
The regularity of radical chemical initiation of emulsion polymerization of diethylethynylcarbinol methacrylic ether in the presence of APPK, OP-10, OS-10E-30 dispersant was studied.
Keywords: monomer, initiation, methacrylic acid chloride, heat resistance, triethylamine, gel effect, diethylethynylcarbinol methacrylic ester. Emulsifier. Emulsion system.